The Use of Complementary and Alternative Medicine Is Less Frequent in Patients with Inflammatory Bowel Disease Than in Patients with Other Chronic Gastrointestinal Disorders - Anna Fábián; Mariann Rutka; Tamás Ferenci; Renáta Bor; Anita Bálint; Klaudia Farkas; Ágnes Milassin; Kata Szántó; Zsuzsanna Lénárt; Ferenc Nagy; Zoltán Szepes; Tamás Molnár (Gastroenterology Research and Practice)
Background and Aims. Complementary and alternative medicine (CAM) is commonly used among patients with inflammatory bowel diseases (IBD), but evidence about its real-life use is limited. We aimed to assess and compare CAM use in outpatients with IBD and other gastrointestinal diseases. Materials and Methods. The use of herbs and botanicals, lifestyle modifications and mind/body therapies, patient satisfaction, and continuous use of conventional medicine were assessed with an anonymous questionnaire at a tertiary IBD unit in Hungary. 396 IBD patients (207 with Crohn’s disease, 185 with ulcerative colitis, and 4 with indeterminate colitis) and 164 patients with gastric acid-related diseases, premalignant and malignant colorectal diseases, lactose intolerance, celiac disease, dysbacteriosis, and so on were included. Results. IBD patients reported significantly lower usage of herbs than did controls (25% versus 42%, p<0.001). More than 90% of responding IBD patients continued conventional medication besides herbal remedies (83% in unaltered doses). IBD patients were more likely to implement lifestyle modifications (77% versus 63%, p=0.0011), but not body/mind therapies (20% versus 15%, p=0.1516). Younger age was a significant predictor of lifestyle modifications (p=0.0246). Conclusions. CAM use (especially that of herbal remedies) in IBD is less frequent than that in other gastrointestinal diseases. It is more a complementary than an alternative to conventional medicine in IBD. There is no significant difference between CAM use in patients with Crohn’s disease and that in patients with ulcerative colitis, although the latter tend to choose herbs; the benefit of which is supported by scientific evidence. This study is registered at the Medical Research Council, Hungary. This trial is registered with 3769/2010/1018EKU.